Imaging of radiation damage using complementary field ion microscopy and atom probe tomography. - Dagan, M; Hanna, L; Xu, A; Roberts, S; Smith, G; Gault, B; Edmondson, P; Bagot, P; Moody, M (Elsevier, 2015)
Radiation damage in tungsten and a tungsten-tantalum alloy, both of relevance to nuclear fusion research, has been characterized using a combination of field ion microscopy (FIM) imaging and atom probe tomography (APT). While APT provides 3D analytical imaging with sub-nanometer resolution, FIM is capable of imaging the arrangements of single atoms on a crystal lattice and has the potential to provide insights into radiation induced crystal damage, all the way down to its smallest manifestation - a single vacancy. This paper demonstrates the strength of combining these characterization techniques. In ion implanted tungsten, it was found that atomic scale lattice damage is best imaged using FIM. In certain cases, APT reveals an identifiable imprint in the data via the segregation of solute and impurities and trajectory aberrations. In a W-5at%Ta alloy, a combined APT-FIM study was able to determine the atomic distribution of tantalum inside the tungsten matrix. An indirect method was implemented to identify tantalum atoms inside the tungsten matrix in FIM images. By tracing irregularities in the evaporation sequence of atoms imaged with FIM, this method enables the benefit of FIM's atomic resolution in chemical distinction between the two species.